SINKRONISASI ANTARA HUKUM PAJAK DENGAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS MENGENAI TANGGUNG JAWAB SOSIAL PERUSAHAAN (CSR) - Anto Sibarani; Bismar Nasution; Mahmul Siregar; Suhaidi Suhaidi (USU LAW JOURNAL, 2014)
ABSTRACTDifferent regulations between Law No. 40 of 2007 on Limited Liability Companies with Tax Law at the expense of corporate social responsibility cause injustice and legal uncertainty for companies that implement CSR, and can trigger the employer conducts tax evasion efforts. Legal research was conducted to determine the synchronization between the Tax Law with Law No. 40 of 2007 on Limited Liability on CSR. Law No. 40 of 2007 on Limited Liability Company requires companies to implement CSR since the start of operations and budgeted at the beginning of the year, although not reaching earnings, while the Law Number 36 Year 2008 regarding Income Tax through Government Regulation No. 93 of 2010 stipulates that only companies that have make a profit in the previous year which may charge CSR.Keywords: CSR, Synchronization, Tax Law